(untitled) (Palíndromo, 2025)
This paper takes an interesting look at the possible places where beauty resides in education and aims at unraveling this concept in its philosophical context to dialogue with education. It methodologically selects theoretical elements, prioritizing the Nietzschean horizon, to some extent respond to the thesis of this paper: does beauty have a place in education? We conclude that we need more pedagogical tools to investigate beauty in education and consider the school as a space of existence, as other instruments are also needed to assess the dynamics of an educational institution. We suspect that our vision is too restricted, there is more beauty in school than we can see, and it will be through a pedagogy of attention, as a gesture capable of interrupting what we believe we know, that we will begin new formative experiences.